Composite outcome measure (COM) and pocket closure as clinical endpoints following treatment of infra bony defects with Guided tissue regeneration and Open flap debridement - Sruthy Tom Thayil; Baiju Radhamoni Madhavan Pillai; Raseena Beevi Nafeesa; Roshna Erumbuzhi Kalarikkal (Wolters Kluwer Medknow Publications, 2022)
Background: Clinical outcomes of regenerative periodontal therapy has been traditionally assessed using surrogate markers, primarily clinical attachment level (CAL) gain and probing pocket depth (PPD) reduction. This study tried to assess newer clinical endpoints namely pocket closure and composite outcome measure (COM) apart from CAL gain, PPD reduction and gingival recession in patients who underwent guided tissue regeneration (GTR) and compared the same with open flap debridement (OFD) six months post treatment. Materials and Methods: Records of 58 sites in 48 patients who had undergone GTR (28 sites) and OFD (30 sites) for infrabony defects were evaluated for CAL gain, PPD reduction, change in GR, FMBS, and FMPS at baseline and 6 months after surgery. Pocket closure and COM were used to assess the efficacy of both treatments. Results: Statistically significant improvements were seen in both the groups except GR from baseline to 6 months. GTR-treated sites showed better improvements with a statistically significant difference in CAL gain after 6 months. Pocket closure and percentage of treatment success and failure in both the groups assessed using a COM were similar and did not differ statistically. Conclusion: Treatment of infrabony defects with GTR combined with a xenograft offers better CAL gain after 6 months compared to OFD alone and also found that baseline PPD and FMBS were the factors determining pocket closure.